Safe Framework: Sharia Super App for Financial Inclusion in Indonesia - Surya Tegar Widjiantoro; Muhammad Irwan Padli Nasution; Muhammad Habibi Siregar (Sharia Economic and Management Business Journal (SEMBJ), 2025)
Background: Despite Indonesia's Muslim population of 207 million, the sharia financial inclusion rate stands at only 13.41%, markedly lagging behind the conventional financial inclusion rate of 80.51%. Meanwhile, 92% of customers of Indonesia's largest Islamic bank already utilize conventional super app ecosystems for daily financial transactions, exposing an architectural gap that remains unaddressed in the academic literature. This study aims to propose the first conceptual framework that positions the sharia super app as an integrated Islamic finance distribution model in Indonesia. Method: The methodology integrates a Systematic Literature Review (SLR) following the PRISMA protocol applied to 39 articles retrieved from Scopus (2016–2026), bibliometric analysis using VOSviewer, and conceptual framework development via a Theory Synthesis approach. Results: The study produces the SAFE Framework (Sharia-Aligned Financial Ecosystem), which positions the sharia super app as the highest manifestation of a Digital Business Ecosystem, integrating seven core services (Islamic banking, sharia e-wallet, sharia investment, digital ZISWAF, sharia peer-to-peer lending, halal marketplace, and Islamic insurance) under a robust sharia governance layer, evaluated through the lens of Maqasid al-Shariah as a normative framework. Conclusion: The study contributes as the first academic work to model the sharia super app as an Islamic finance distribution channel in Indonesia, to operationalize Maqasid al-Shariah as an evaluative instrument for Islamic fintech ecosystem design, and to provide a realistic implementation blueprint for practitioners, regulators, and future researchers.